The Influence of Emotional Intelligence, Integrity, and Interpersonal Communication on the Performance of Employees - Zaitun Faridah; Syahrir Mallongi; M. Mapparenta (Golden Ratio of Mapping Idea and Literature Format, 2025)
This study aims to investigate the relationship between Emotional Intelligence, Integrity, and Interpersonal Communication and the Performance of Representative Employees of the National Population and Family Planning Agency in South Sulawesi Province. The data in this study were obtained from employees at the Representative Office of the National Population and Family Planning Agency of South Sulawesi Province in 2025, who were willing to participate as respondents. This study utilizes primary data collected through direct research in the field, where questionnaires and statement sheets were provided to respondents. A sample size of 94.35 was obtained using the Slovin formula, indicating that the researcher requires 94.35 samples for this study, which will be rounded to 95 respondents. The data analysis technique employed descriptive statistical analysis and SPSS 26.0. The results of the hypothesis test show that Emotional Intelligence has a positive and significant effect on Employee Performance. The better the Emotional Intelligence, the better the employee level. Integrity has a positive and significant effect on Employee Performance; the better the level of Integrity, the better the level of employees in the Representative of the National Population and Family Planning Agency of South Sulawesi Province. Interpersonal Communication has a positive and significant effect on Employee Performance. The better the interpersonal communication, the higher the level of employees at the Representative of the National Population and Family Planning Agency of South Sulawesi Province.